2010
DOI: 10.3141/2181-01
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Permanent Deformation of Asphalt Mixtures Based on Shear Properties

Abstract: A permanent deformation model was developed in this study on the basis of shear properties of asphalt mixtures, such as cohesion and friction angle. Two types of laboratory tests—triaxial compressive strength test and repeated load permanent deformation test—for three types of asphalt mixtures with various volumetric properties were performed to correlate the shear properties with rutting performance. A rational approach was proposed to determine flow number (FN) more accurately with the Hoerl model and roughn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…In the previous study, RLPD test results revealed an excellent exponential correlation between τ/τ f and permanent strain ⑀ p under certain load repetitions (10). From laboratory test data, a permanent deformation model based on τ/τ f was proposed:…”
Section: Review Of Previous Modelmentioning
confidence: 98%
See 4 more Smart Citations
“…In the previous study, RLPD test results revealed an excellent exponential correlation between τ/τ f and permanent strain ⑀ p under certain load repetitions (10). From laboratory test data, a permanent deformation model based on τ/τ f was proposed:…”
Section: Review Of Previous Modelmentioning
confidence: 98%
“…The authors previously proposed a permanent deformation model based on a ratio of shear stress to strength (10). The shear strength of a material is principally developed from two sources: cohesion c (kPa) and friction angle φ (°) (1): where τ f is shear strength at failure and σ f is normal stress at failure.…”
Section: Review Of Previous Modelmentioning
confidence: 99%
See 3 more Smart Citations